Peningkatan kapasitas pengurus BUMDES dalam penyusunan proposal bisnis di Kabupaten Pacitan - Irawan, Ferry; Firmansyah, Amrie; Wijaya, Suparna; Jubaedah, Jubaedah (Pengmasku, 2025)
This community service activity focuses on improving the capacity of Village-Owned Enterprises (BUMDes) managers in preparing effective business proposals. The program involves 100 BUMDes, consisting of Start-Up and Developing BUMDes in Pacitan Regency, with the aim of strengthening village economic independence through more professional business management. In this program, participants receive training covering crucial aspects of business proposal preparation, including market analysis, financial projections, and marketing strategies. This assistance not only aims to enhance the technical skills of BUMDes managers but also helps them prepare strategic documents capable of attracting external funding. The results of the activity show a significant improvement in the quality of the business proposals prepared, where the proposals are now more structured and include more comprehensive analyses. In addition, the use of digital technology in marketing was also part of the training, which is expected to expand market access for the products and services offered by BUMDes. Through this activity, it is hoped that BUMDes in Pacitan Regency can develop more independently and professionally and become key drivers of sustainable village economic development.